Meningkatkan Kemampuan Membaca Menggunakan Metode Kontekstual Berbantuan Media Buku Bergambar : Penelitian Tindakan Kelas I di SDN Linggajaya - Ici Sulistiawati; Riga Zahara Nurani, Ade Maftuh (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study is based on the problem of students who are less able to read in learning Indonesian. This study aims to improve reading skills in Indonesian subjects by using contextual methods assisted by picture book media. Based on the results of the study, students' reading skills are still difficult to recognize letters, connect sounds with letters, and read simple words. The research method used is classroom action research (PTK) which consists of planning, action, observation, reflection in each cycle. The subjects in this study were 22 students. The results of this study state that READING ABILITY USING CONTEXTUAL METHODS ASSISTED BY BOOK MEDIA Based on the results of the first cycle of research, there were 16 students with a percentage of 72.72% who got scores reaching KKM, while 6 students with a percentage of 27.27% had not reached the KKM score, with an average score of speaking skills test results of 77.04. and cycle II showed that there were 22 students with a percentage of 87.72% who got scores reaching the KKM, while 2 students with a percentage of 9.09% had not reached the KKM score, with an average score of reading skills test results of 90.90%. Through this study, it can be concluded that the contextual method with the help of book media is effective in improving students' reading skills in class I of Sdn Lingga Jaya, so it can be used as an alternative in the Indonesian language learning process.